Molecular identification and thermoresistance to boiling of Nocardia farcinica and Nocardia cyriacigeorgica from bovine bulk tank milk - Condas, L. A. Z. [UNESP] (2012)
Two strains of Nocardia spp. were isolated from bovine milk of two individual bulk tank. Molecular identification classified the strains as Nocardia farcinica and Nocardia cyriacigeorgica. The thermorresistance to boiling of the isolates was carried out and was observed bacterial growth after boiling. Our findings indicate the potential risk of pathogen transmission to humans through contaminated milk with Nocardia spp.